1996
DOI: 10.1002/(sici)1097-4652(199612)169:3<439::aid-jcp4>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Balanced mechanical forces and microtubule contribution to fibroblast contraction

Abstract: Fibroblast locomotion is thought to generate tractional forces which lead to contraction and reorganisation of collagen in tissue development and repair. A culture force monitor device (CFM) was used to measure changes in force in fibroblast populated collagen lattices, which resulted from cytoskeletal reorganisation by cytochalasin B, colchicine, vinblastine, and taxol. Microfilament disruption abolished contraction forces, microtubule disruption elicited a new peak of contraction, while taxol stabilisation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 28 publications
2
33
0
1
Order By: Relevance
“…Either nocodazole or taxol blocked formation of fibroblast dendritic extensions in relaxed collagen matrices, which was important because nocodazole might have interfered with extensions by stimulating fibroblast contraction (25,26). Taxol, on the other hand, can block microtubule dynamics (27,28) without simultaneously increasing cell contraction (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Either nocodazole or taxol blocked formation of fibroblast dendritic extensions in relaxed collagen matrices, which was important because nocodazole might have interfered with extensions by stimulating fibroblast contraction (25,26). Taxol, on the other hand, can block microtubule dynamics (27,28) without simultaneously increasing cell contraction (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Taxol, on the other hand, can block microtubule dynamics (27,28) without simultaneously increasing cell contraction (25,26). Also, microtubules were required for fibroblast spreading in relaxed collagen matrices regardless of whether cells were stimulated with PDGF or LPA.…”
Section: Discussionmentioning
confidence: 99%
“…Although microtubules themselves do not generate contractile forces, it has been noticed that microtubule depolymerization induces the formation of actin stress fibers and cell contraction (Danowski, 1989;Brown et al, 1996;Verin et al, 2001;Birukova et al, 2004b). However, in spite of the apparent universality of this phenomenon, the molecular basis by which microtubule disassembly stimulates cell contractility is not clearly established.…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising, since active and passive cellular biomechanics based on the stability provided by the cytoskeleton impacts many essential cellular functions. In addition to the role of the cytoskeleton in cellular motility and division (11,12), it has been shown that a functionally intact cytoskeleton is crucial to build up contraction forces in a three-dimensional collagen lattice (13,14). These cell functions are essential for the homeostasis of the extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, there are many cells able to perform mechanical work, for example, muscle cells or cells of connective tissues that are connected to the proteins of the ECM. Three-dimensional collagen lattices seeded with fibroblasts have been used to analyze the effect of actin or microtubule disruption on the mechanical activity of cells (13,14). The mechanical properties of cells and the state of the cytoskeleton affect the interaction between fibroblasts and the ECM (30)(31)(32), so mechanical changes may reveal new aspects of the age-related degradation of the elastic properties of the dermis.…”
Section: Introductionmentioning
confidence: 99%